Fed QE and lending behaviour: a heterogeneity analysis of asset purchases - Kapoor, Supriya; Grimaldi, Marianna Blix (Working Paper Series 428, Sveriges Riksbank (Central Bank of Sweden), 2023)
Though unconventional monetary policy is still new, already there is a conventional wisdom that the impact of monetary policy is related to the composition of the asset mix. This turns out to be incomplete and potentially misleading. In this paper, we find more complex effects on bank lending from Quantitative Easing (QE) introduced by the Federal Reserve Bank in 2008. The novelty of our approach is to augment the model with bank-level heterogeneity. While there is a relation between lending and the type of assets purchased by the central bank, the impact on similarly QE-exposed banks is also crucially dependent on banks' solvency and liquidity exposures. Our results highlight that it is necessary to take heterogeneity of exposure into account when assessing the effects of QE.
WORKING PAPER
Keywords: large-scale asset purchases, Federal Reserve, quantitative easing, heterogeneity, liquidity, solvency; Banking; CENTRAL BANKS; FINANCIAL INSTITUTIONS; Finance; Financial economics, Financial and statistical analysis; Macroeconomics, open economy, international; bank lending; economics and finance; Policy